Forensic investigation of ettringite formation in hardened mass concrete structures - Tong, Xiao Qing (2016)
Mass concrete has always been associated with large structures of large volume placements. Placement of mass concrete generates temperature high enough to damage the concrete. The chemical reaction between cement and water is an exothermic process where a large amount of heat is generated. Heat escapes more slowly than it is generated in a mass concrete placement. If the internal temperature reaches more than 70°C, it affects the long term durability of concrete by Delayed Ettringite Formation (DEF). DEF is widely known to cause cracking and spalling of concrete by non-uniform expansion in hardened concrete. The report will assess the existence of defects in the hardened concrete by carrying out analysis and examination. Samples are extracted by coring at a confined area on a foundation slab in Vietnam. The foundation slab has a massive volume of 8200 m3. Temperature sensor has detected certain areas within the foundation slab reaches a high early temperature of 90°C. In the interest of exploring the microstructure of the core samples to identify the presence of ettringite, Field Emission Scanning Electron (FESEM) was carried out. Additionally, Energy Dispersive X-Ray (EDX) was used to determine the element composition of the core sample in order to give more information to conclude on the presence of ettringite. Compressive strength test is performed on core samples to find out its compressive strength after two years from its placing date. The values obtained are compared with data from Vietnam and project from past year. Identification of ettringite present in the core samples will be concluded with results obtained from the abovementioned tests.